THE USE OF PODCATS-BASED EDUCATIONAL SOCIAL MEDIA IN TEACING FIQH THAHARAH AT ISLAMIC BOARDING SCHOOLS - Sirajuddin; Zulfannur; Yusnaini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The development of digital technology has influenced various aspects of education, including Islamic education in Islamic boarding schools. One of the challenges faced by Islamic boarding schools is adapting teaching methods to the characteristics of students in the digital age without losing traditional values. This educational service activity aims to utilize educational social media based on podcasts to support Fiqh learning, particularly thaharah material, in Islamic boarding schools. The method used is a participatory educational service approach with an implementative model that actively involves students and educators in the planning, implementation, and evaluation stages. Data collection techniques include observation, questionnaires, and interviews, which are analyzed descriptively. The results of the activity show that the use of podcasts contributes positively to improving students' understanding of Fiqh thaharah and increasing their involvement in the learning process. Thus, educational podcasts can be an effective supporting medium for Fiqh learning in Islamic boarding schools.